Peran Lembaga Bantuan Hukum Kampus di Perguruan Tinggi Keagamaan Islam Negeri dalam Bantuan Hukum Litigasi dan Non Litigasi terhadap Masyarakat Miskin - Hariyanto Hariyanto (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
This study tried to determine the role of the two Legal Aid equally campusbased in its efforts to help the poor in legal aid in the field of litigation and nonlitigation. The study, which covered include the role of LPKBHI IAIN Walisongo andLKBH STAIN Purwokerto, case handling procedures, and constraints facedLPKBHI IAIN Walisongo and LKBH STAIN Purwokerto and strategies used toaddress them. This study used juridical empirical approach to comparative analysis.The findings of this study indicate that the difference between LPKBHI IAINWalisongo and LKBH STAIN Purwokerto. Among them are LPKBHI IAINWalisongo impure prodeo as ordered by Law No. 16 of 2011. LKBH STAINPurwokerto is still lacking good human resources, finance and facilities. Difference innumber of clients between the two Legal Aid Society very much, showing thatLPKBHI IAIN Walisongo more widely known by the public, it is believed in playingthe service function of law for the people. In the case, the Legal Aid is in principle thesame in terms of client service procedures both non-litigation and litigation. But in theactualization, LKBH STAIN Purwokerto still difficulties in maximizing its rolebecause it is hampered by many constraints both internal and external. WhileLPKBHI IAIN Walisongo, the problem is the performance of each division are lessthan the maximum, many administrators who served on the faculty, most of the board'slack of commitment. Meanwhile, the strategies used to overcome them; LPKBHIIAIN Walisongo build an extensive network with several organizations that producestrategic collaborations, the support of institutions that provided the impetus for gaitLPKBHI in giving legal aid. Average LKBH STAIN Purwokerto DIPA to requestfunds from the campus, asking for help Advocates from the outside (especially from thealumni).